Developing a structural model to assess students’ knowledge- attitudes towards sustainability - Abdul Aziz, Azmahani (2012)
This paper presents results of a study in developing a structural model of assessing engineering students’ knowledge-attitude towards sustainability. A model of knowledge-attitude with the smallest number of parameters that adequately describes the observed covariance structure was developed using the structural equation model (SEM). Results showed the structural model was reliable and in agreement to identify the influence of knowledge on attitude towards sustainability among engineering students. It was found that the basic knowledge on sustainable development have a strong correlation to develop and improve students’ attitude. It is proposed the model can be used as a tool for lecturers to identify important elements on sustainable development they need to address in preparing lecture materials.